Resveratrol Ameliorates Cardiac Hypertrophy by Down‐regulation of miR‐155 Through Activation of Breast Cancer Type 1 Susceptibility Protein. Issue 4 (April 2016) - Fan, Yuhua; Liu, Li; Fang, Kun; Huang, Tao; Wan, Lin; Liu, Youbin; Zhang, Sen; Yan, Dongxia; Li, Guangnan; Gao, Yanhui; Lv, Yanjie; Chen, Yanjun; et al.
Abstract : Background: The polyphenol resveratrol (Rev) has been reported to exhibit cardioprotective effects, such as inhibition of TAC (transverse aortic constriction) or isoprenaline (ISO)‐induced hypertrophy. MicroRNA‐155 (miR‐155) was found to be decreased in hypertrophic myocardium, which could be further reduced by pretreatment of Rev. The study was designed to investigate the molecular effects of miR‐155 on cardiac hypertrophy, focusing on the role of breast cancer type 1 susceptibility protein (BRCA1). Methods and Results: We demonstrated that Rev alleviated severity of hypertrophic myocardium in a mice model of cardiac hypertrophy by TAC treatment. Down‐regulation of miR‐155 was observed in pressure overload– or ISO‐induced hypertrophic cardiomyoctyes. Interestingly, administration of Rev substantially attenuated miR‐155 level in cardiomyocytes. In agreement with its miR‐155 reducing effect, Rev relieved cardiac hypertrophy and restored cardiac function by activation of BRCA1 in cardiomyoctyes. Our results further revealed that forkhead box O3a (FoxO3a) was a miR‐155 target in the heart. And miR‐155 directly repressed FoxO3a, whose expression was mitigated in miR‐155 agomir and mimic treatment in vivo and in vitro. Conclusions: We conclude that BRCA1 inactivation can increase expression of miR‐155, contributing to cardiac hypertrophy. And Rev produces their beneficial effects partially by down‐regulating miR‐155 expression, which might be a novel strategy for treatment of cardiac hypertrophy.